2019
DOI: 10.1186/s12893-019-0523-7
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal skin tensile strength in aesthetic and massive weight loss patients and its role in ventral hernia repair

Abstract: Background Clarifying the biomechanics of abdominal skin could lead to different uses for this tissue such as the ventral repair of hernias in patients with excess skin and incisional hernias. The objective of this study was to compare the maximum tensile strength of abdominal skin to commercial meshes and to verify whether or not it varies between aesthetic patients and massive weight-loss patients. Methods Experimental cross-sectional study. Skin samples sized 32 × 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Pannucci et al 4 previously reported a 6.8 percent risk of clinically relevant bleeding in patients who received enoxaparin 40 mg twice daily. Importantly,…”
Section: Disclosurementioning
confidence: 96%
See 1 more Smart Citation
“…Pannucci et al 4 previously reported a 6.8 percent risk of clinically relevant bleeding in patients who received enoxaparin 40 mg twice daily. Importantly,…”
Section: Disclosurementioning
confidence: 96%
“…If sufficient quality dermis is available as a donor tissue, however, it is certainly a potentially low-cost option. Abdominal dermis has similar or higher tensile strength compared to even some synthetic meshes, 4 but it can be prone to stretch and expansion when tension is applied, which can lead to bulging or hernia recurrence.…”
mentioning
confidence: 99%
“…Biomechanical studies performed on full-skin and dermal collagen separately give almost identical results. The mechanical properties of the dermis, in turn, depend on the structure, density and direction of collagen fibres [6,22,23].…”
Section: Fig 1 Stages Of Skin Deformationmentioning
confidence: 99%
“…Each biological tissue is able to acquire deformation properties to stretch or contract. At each stage of deformation changes in histoarchitectonics (reversible -within the plastic characteristics, irreversible -outside these parameters) are revealed in the tissues of different topographic and anatomical areas, which to some extent affect the physiological and functional mechanisms of the tissue [22,24].…”
Section: Fig 1 Stages Of Skin Deformationmentioning
confidence: 99%